Pengaruh E-Commerce, Penggunaan Sistem Informasi Akuntansi, Ketersediaan Modal, Dan Dukungan Keluarga Dalam Pengambilan Keputusan Untuk Berwirausaha Pada Mahasiswa STIE AMM Mataram - Nur Islamiyah; Ida Ayu Nursanty; M. Wahyullah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2026)
This study aims to analyze the influence of e-commerce, the use of accounting information systems, capital availability, and family support on entrepreneurial decision-making among students at STIE AMM Mataram. The research variables consist of four independent variables, namely e-commerce (X₁), use of accounting information systems (X₂), capital availability (X₃), and family support (X₄), as well as one dependent variable, entrepreneurial decision-making (Y). The population of this research includes all active students of STIE AMM Mataram. At the same time, the sample was determined using purposive sampling with the criteria of accounting students who had taken courses in Accounting Information Systems and Entrepreneurship. Based on these criteria, 58 respondents were obtained. Data were collected via an online questionnaire (Google Forms) and analyzed in SPSS 25 using classical assumption tests and multiple linear regression. The results show that, partially, e-commerce (X₁) and the use of accounting information systems (X₂) have a positive and significant effect on entrepreneurial decision-making, while capital availability (X₃) and family support (X₄) do not have a significant effect. Simultaneously, the four independent variables jointly have a significant effect on students’ entrepreneurial decision-making.